Novel mechanism for reverse transcription in hepatitis B viruses. - Wang, G H (1993)
Reverse transcription of all retroviruses and most retroid elements requires tRNA as a primer for DNA synthesis. However, in hepatitis B viruses the viral polymerase itself acts as a primer for reverse transcription (G.-H. Wang and C. Seeger, Cell 71:663-670, 1992). We have now demonstrated that in order to prime DNA synthesis, the polymerase binds to an RNA hairpin, which then serves as a template for the formation of a short DNA primer that is covalently linked to protein. Following its synthesis, the nascent DNA strand apparently dissociates from its template and reanneals with complementary sequences at the 3' end of the RNA genome, where DNA synthesis continues. Since this RNA hairpin also functions as a packaging signal for viral RNA, hepadnaviruses have adopted a replication strategy that relies on the same signal for two biochemically distinct events, RNA packaging and reverse transcription. This mechanism is without precedent among all known retroid elements and among other viruses and bacteriophages that use protein as a primer for RNA or DNA synthesis. It could provide an effective target for antiviral therapy, which is required for the treatment of more than 300 million carriers of hepatitis B virus.